2022
DOI: 10.1055/s-0040-1718236
|View full text |Cite
|
Sign up to set email alerts
|

Interfascicular Gliding Dysfunction Relation with Focal Neuropathy in Diabetic Patients with Carpal Tunnel Syndrome

Abstract: Carpal tunnel syndrome (CTS), a common neuropathy of the upper limb, is highly prevalent in diabetic patients. Recent findings indicate that changes in median nerve elasticity and its gliding characteristics may contribute to the development of CTS. Normally, each nerve should be able to adapt to the positional changes by passive movement relative to the surrounding tissues. This ability is provided by a gliding apparatus around the nerve trunk in the surrounding soft tissue. The fascicles of nerve trunks can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…At very low concentrations of insulin, the quality of bone expressed as skeletal microarchitecture is impaired, due to a decrease in the intensity of bone formation or a reduction of the RUNX2 factor (a marker of osteogenesis). Insulin supply improves bone microarchitecture [74]. The latest data revealed that patients with T2DM using insulin therapy have an increased risk of fractures [60].…”
Section: Treatment Of Type 2 Diabetes and Its Influence On Bone Metab...mentioning
confidence: 99%
“…At very low concentrations of insulin, the quality of bone expressed as skeletal microarchitecture is impaired, due to a decrease in the intensity of bone formation or a reduction of the RUNX2 factor (a marker of osteogenesis). Insulin supply improves bone microarchitecture [74]. The latest data revealed that patients with T2DM using insulin therapy have an increased risk of fractures [60].…”
Section: Treatment Of Type 2 Diabetes and Its Influence On Bone Metab...mentioning
confidence: 99%